Trade and Economic Effects of IRC Further Empirical Evidence from SPS and TBT Provisions - Disdier, Anne-Célia (OECD Publishing, 2019)
Cutting trade costs, especially those stemming from non-tariff measures, is a growing priority for policy makers. One way to achieve this is for countries to improve their co-operation on regulatory matters. An avenue open to governments is to include provisions related to international regulatory co-operation (IRC) into preferential trade agreements (PTAs). However, there exists little empirical evidence of the benefits of these co-operative mechanisms. This paper provides this evidence, in the context of Sanitary and Phytosanitary (SPS) and Technical Barriers to Trade (TBT) provisions. It measures the effect of IRC mechanisms on trade flows using the latest developments in the gravity literature and the most recent data sources. The work distinguishes between different forms of co-operation implemented between countries within PTAs while also accounting for the level of commitment between partners. The estimation results suggest that PTAs including SPS and TBT measures have a significant and positive effect on trade flows, with the legal enforceability of IRC mechanisms having the strongest and most robust impact on trade flows. This result holds even when WTO-related provisions and dispute settlement procedures are controlled for, implying that binding commitments are important in maximizing post-PTA trade flows. The work shows that transparency and co-operation are significant and robust factors in increasing trade. It also reinforces the view that the impact takes some time to materialise, which is important when evaluating the effectiveness of deep IRC mechanisms
Keywords: Trade